Esophageal Dilation in Children: A State of the Art Review. Issue 1 (19th January 2023) - Shahein, Abdul R.; Krasaelap, Amornluck; Ng, Kenneth; Bitton, Samuel; Khan, Muhammad; Manfredi, Michael A.; Lerner, Diana G.
Abstract : Esophageal dilations in children are performed by several pediatric and adult professionals. We aim to summarize improvements in safety and new technology used for the treatment of complex and refractory strictures, including triamcinolone injection, endoscopic electro-incisional therapy, topical mitomycin-C application, stent placement, functional lumen imaging probe assisted dilation, and endoscopic vacuum-assisted closure in the pediatric population.